Sustained, complete response to pexidartinib in a patient with CSF1R‐mutated Erdheim–Chester disease. Issue 3 (3rd January 2022) - Abeykoon, Jithma P.; Lasho, Terra L.; Dasari, Surendra; Rech, Karen L.; Ranatunga, Wasantha K.; Manske, Michelle K.; Tischer, Alexander; Ravindran, Aishwarya; Young, Jason R.; Tobin, William Oliver; Flanagan, Eoin P.; Nowakowski, Kevin E.; et al.
Abstract: Erdheim–Chester disease (ECD) is a histiocytic neoplasm that predominantly harbors mitogen‐activated protein kinase (MAPK) pathway variants. MAPK inhibitors typically are effective treatments, but mutations outside the MAPK pathway, such as CSF1R variants, may cause refractory ECD. We describe a patient with a novel somatic mutation in CSF1R ( CSF1R R549_E554delinsQ ) that resulted in refractory ECD affecting the central nervous system. Cell model studies, RNA sequencing analysis, and in silico protein modeling suggested that she had a gain‐of‐function mutation occurring in a region critical for autoinhibition. The patient was treated with pexidartinib, a CSF1R inhibitor, and has had a complete clinical and metabolic response lasting more than 1.5 years to date. To our knowledge, this is the first report to describe successful treatment of a patient with ECD by using an agent that specifically targets CSF1R. This case also highlights the critical role of individualized molecular profiling to identify novel therapeutic targets in ECD.